2016
DOI: 10.1007/978-3-319-42267-1
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Mathematics Education

Abstract: use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…In our original pre-ICME-13 assessment of the State of the art (Williams et al, 2016), we commented on key weaknesses in the field that research needed to address, and this book does address some of these, such as the clarification of the conceptions in the field and its theoretical bases; the different integrative and cross curricular practices studied in cases; and the policies adopted in schools breaking down disciplinary barriers.…”
mentioning
confidence: 99%
“…In our original pre-ICME-13 assessment of the State of the art (Williams et al, 2016), we commented on key weaknesses in the field that research needed to address, and this book does address some of these, such as the clarification of the conceptions in the field and its theoretical bases; the different integrative and cross curricular practices studied in cases; and the policies adopted in schools breaking down disciplinary barriers.…”
mentioning
confidence: 99%
“…Following Choi and Pak (2006), Stock andBurton (2011), andWilliams et al (2016), we recognize various levels of the term interdisciplinarity which, we use in its broadest sense.…”
Section: Development Of Teaching Materialsmentioning
confidence: 99%
“…In a review, Williams et al (2016) concluded that interdisciplinary mathematics education in the context of inquiry and problem solving offers mathematics to the wider world in the form of added value (e.g. in problem solving), but on the other hand also offers to mathematics the added value of the wider world.…”
Section: Codamentioning
confidence: 99%
“…The problem of interdisciplinary mathematics education requires a conceptualisation of 'discipline' or 'disciplinarity'. But first, assuming an everyday, intuitive notion of discipline, we reflect on the issue of 'inter' disciplinarity: in fact, interdisciplinarity is often understood as a multifaceted but partially nested system of concepts, where different forms of inquiry are situated, at one or another level of complexity of the inquiry process, as follows (see a more extensive discussion of this in Williams et al, 2016) (Fig. 3.1).…”
Section: Introduction To Interdisciplinaritymentioning
confidence: 99%